Concrete performance with addition of bamboo ash (Research, Society and Development, 2020)
This research aims to analyze the performance of concrete with addition of bamboo ash, check the consistency obtained after the curing process, determine the compressive strength at 28 days of curing, evaluate the water absorption capacity and the voids index conventional and gray concrete. 20 specimens were molded and the data collection was done through laboratory tests. The percentages replaced by cement with ash were 0.5%, 1.0% and 1.5%. As the material added is highly pozzolanic, it was previously ground to increase the degree of fineness and, thus, its granulometry was compatible with that of cement. The results obtained, for the trace of 1.5% ash, showed the greatest workability with 50.75% more consistent than the conventional one. Regarding strength, the traces with contents of 0.5% and 1.0% of BW were satisfactory reaching about 9.5% and 3%, respectively, more favorable compared to the reference concrete. The 1.5% had a resistance deficit of 2.5%, compared to the conventional one. Regarding absorption, the trace with 1.5% ash was the one that obtained the best absorption index (1.25%). In relation to the void’s indices, the traces with CB were not conclusive. Thus, it can be concluded that the fluidity of the cementitious matrix is improved with the addition of ash and that concretes with these additions tend to be more durable.